Respostas
respondido por:
2
a)
log₂(x + 2) = 3
x + 2 = 2³
x + 2 = 8
x = 8 - 2
x = 6
b)
log₅(x² + x - 6) = log₅(3x + 2)
x² + x - 6 = 3x +2
x² - 3x + x - 6 - 2 = 0
x² - 2x - 8 = 0
a = 1, b = - 2, c = - 8
Δ = b² - 4ac
Δ = (- 2)² - 4.1.(- 8) = 4 + 32 = 36
x₁ = - b + √Δ
2a
x₁ = - (- 2) + √36 = 2 + 6 = 8 = 4
2.1 2 2
x₂ = - b - √Δ
2a
x₂ = - (- 2) - √36 = 2 - 8 = - 6 = - 3
2.1 2 2
Contudo, para x = - 3, temos:
log₅(3.(- 3) + 2) = log₅(-9 + 2) = log₅( - 7) não existe.
então.
x = 4
log₂(x + 2) = 3
x + 2 = 2³
x + 2 = 8
x = 8 - 2
x = 6
b)
log₅(x² + x - 6) = log₅(3x + 2)
x² + x - 6 = 3x +2
x² - 3x + x - 6 - 2 = 0
x² - 2x - 8 = 0
a = 1, b = - 2, c = - 8
Δ = b² - 4ac
Δ = (- 2)² - 4.1.(- 8) = 4 + 32 = 36
x₁ = - b + √Δ
2a
x₁ = - (- 2) + √36 = 2 + 6 = 8 = 4
2.1 2 2
x₂ = - b - √Δ
2a
x₂ = - (- 2) - √36 = 2 - 8 = - 6 = - 3
2.1 2 2
Contudo, para x = - 3, temos:
log₅(3.(- 3) + 2) = log₅(-9 + 2) = log₅( - 7) não existe.
então.
x = 4
DeborahSouza16:
c- log2
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás